2022
DOI: 10.4103/1673-5374.327329
|View full text |Cite
|
Sign up to set email alerts
|

Application of neurotrophic and proangiogenic factors as therapy after peripheral nervous system injury

Abstract: The intrinsic ability of peripheral nerves to regenerate after injury is extremely limited, especially in case of severe injury. This often leads to poor motor function and permanent disability. Existing approaches for the treatment of injured nerves do not provide appropriate conditions to support survival and growth of nerve cells. This drawback can be compensated by the use of gene therapy and cell therapy-based drugs that locally provide an increase in the key regulators of nerve growth, including neurotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 119 publications
0
13
0
2
Order By: Relevance
“…As the most abundant and widely expressed trophic factor in the developing and mature mammalian brain [ 20 ], BDNF supports neuronal survival by regulating their growth, maturation (differentiation), and maintenance [ 20 ]. In this study, we found that malathion did not significantly increase BDNF protein levels in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…As the most abundant and widely expressed trophic factor in the developing and mature mammalian brain [ 20 ], BDNF supports neuronal survival by regulating their growth, maturation (differentiation), and maintenance [ 20 ]. In this study, we found that malathion did not significantly increase BDNF protein levels in the rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral neuropathy is one of the typical chronic complications of diabetes, approximately 50% of adult patients suffering from diabetes developed various degrees of peripheral neuropathy in their lifetime (31). Dorsemans et al (32) found that acute and chronic hyperglycemia impaired the regeneration and de novo formation of zebrafish neuronal cells, resulting to adverse effects on neurogenesis and brain healing.…”
Section: Protective Effect Of Peripheral Motor Nervementioning
confidence: 99%
“…Angiogenesis is a co-regulated and balanced process of pro-angiogenic factors [e.g., vascular endothelial growth factor A (VEGFA), fibroblast growth factor 2 (FGF2) and hepatocyte growth factor (HGF)] and anti-angiogenic factors [e.g., angiostatin, vasohibin 1 (VASH1) and thrombospondins (TSP)] (7,(11)(12)(13). To date, numerous studies have been conducted to understand the roles of these angiogenic factors in the pro-angiogenic and anti-angiogenic therapy (11,12,(14)(15)(16). However, the regulation of these gene expressions during angiogenesis has not been extensively elucidated.…”
Section: Znf667 Facilitates Angiogenesis After Myocardial Ischemia Th...mentioning
confidence: 99%